Effect of Adjuvant Homeopathy with Usual Care in Management of Thrombocytopenia Due to Dengue: A Comparative Cohort Study - Nayak, Debadatta; Chadha, Vishal; Jain, Shruti; Nim, Priyanka; Sachdeva, Jyoti; Sachdeva, Garima; Vivekanand, Kumar; Khurana, Anil; Raheja, Sunil M.; Manchanda, Raj K. (Homeopathy, 2019)
Background Dengue is an emerging threat to public health. At present, no clear modalities are available for the prevention and management of thrombocytopenia due to dengue. This article reports the clinical outcomes of integrative homeopathic care in a hospital setting during a severe outbreak of dengue in New Delhi, India, during the period September to December 2015.Methods Based on preference, 138 patients received a homeopathic medicine along with usual care (H+UC), and 145 patients received usual care (UC) alone. Assessment of thrombocytopenia (platelet count < 100,000/mm3) was the main outcome measure. Kaplan–Meier analysis enabled comparison of the time taken to reach a platelet count of 100,000/mm3.Results There was a statistically significantly greater rise in platelet count on day 1 of follow-up in the H+UC group compared with UC alone (mean difference = 12,337; 95% confidence interval [CI], 5,421 to 19,252; p = 0.001). This trend persisted until day 5 (mean difference = 14,809; 95% CI, 1,615 to 28,004; p = 0.02). The time taken to reach a platelet count of 100,000/mm3 was nearly 2 days earlier in the H+UC group compared with UC alone (H+UC: 3.44 days ± standard error of the mean [SEM] 0.18; 95% CI, 3.08 to 3.80; UC: 5.28 days ± SEM 0.29; 95% CI, 4.71 to 5.86; p < 0.001).Conclusion These results suggest a positive role of adjuvant homeopathy in thrombocytopenia due to dengue. Randomized controlled trials may be conducted to obtain more insight into the comparative effectiveness of this integrative approach.
Keywords: dengue; thrombocytopenia; homeopathy; Crotalus horridus